Apocalyptic thinking in early Judaism : engaging with John Collins' The Apocalyptic imagination - Wassen, Cecilia, 1962- (Supplements to the Journal for the Study of Judaism, 2017)
It has been over 30 years since John Collins' seminal study The Apocalyptic Imagination first came out. In this timely volume, Apocalyptic Thinking in Early Judaism: Engaging with John Collins' The Apocalyptic Imagination , leading international experts of Jewish apocalyptic critically engage with Collins' work and add to the ongoing debate with articles on current topics in the field of apocalyptic studies. The subjects include the genre and sub categories of apocalypses, demonology, the character of dream visions, the books of Enoch, the significance of Aramaic texts, and apocalyptic traditions in the Dead Sea Scrolls as well as in Paul's writings. The volume ends with Collins' response to the articles.